Funkcjonowanie zwrotów leżeć bykiem i leżeć martwym bykiem w polszczyźnie - Ignatowicz-Skowrońska, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article discusses the motivation and the functioning of two phraseological units in the Polish language, namely leżeć bykiem (to idle lazily) and leżeć martwym bykiem (to be resting idly). Resulting from independent derivations, they appeared in the Polish language in the second half of the twentieth century. Due to formal similarity, though, they quickly developed relations which led to the transformations of their meaning and form.